PERBEDAAN EFEKTIVITAS KOMPRES DAUN BRASSICA OLERACEAVAR CAPITATA DENGAN KOMPRES HANGAT TERHADAP KELANCARAN ASI IBU NIFAS FASE LETTING GO: The Difference Between Effectiveness of Brassica Oleracea Varian Capitata Compresses and Warm Compresses on Breastfeeding Smoothness in Letting Go Phase of Postpartum Mothers - Endah Susanti; Dily Ekasari; Liya Ni’matul Maula; Astri Yunita; Nanang Muhibbudin (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
As a mother, of course you will give the best, including exclusive breastfeeding for your beloved baby. One of the failures in breastfeeding is due to breast swelling. Cabbage leaves contain sinigrin (allylisothiocyanate) rapine, mustardoil, magnesium, oxilate and sulfur. The purpose of this study was to determine the effectiveness of cabbage compresses and warm compresses on the smoothness of postpartum breastfeeding. The research method used was a quasy experimental study with a pretest-posttest design without a control group design. The study population was mothers who gave birth after 10 days in the working area of the Bendo Community Health Care Center, Pelem Village, Pare District, Kediri Regency with a total of 30 respondents. Respondents were divided into 2 groups, namely postpartum mothers in the cabbage compress intervention group and 15 postpartum mothers in the control group (warm compresses). The sampling technique is total sampling. Analysis using the Wilcoxon statistical test. Based on the research results it is known that the results of data analysis using the Mann-Whitney test show that the Asymp. Sig (2-tailed): 0.003 with an error level of 5% (0.05). These results indicate that the Asymp. Sig (2-tailed) > error rate (pvalue >a). So H0 is accepted and H1 is rejected, which means that there is no significant difference between cabbage leaf compresses and warm compresses on the smoothness of breastfeeding in the letting go phase of postpartum mothers.